An elastoviscoplastic model for porous single crystals at finite strains and its assessment based on unit cell simulations. (September 2016) - Ling, Chao; Besson, Jacques; Forest, Samuel; Tanguy, Benoît; Latourte, Felix; Bosso, Elodie
Abstract: An elastoviscoplastic model is formulated at finite strains for porous single crystals. The model extends the yield function developed by Han et al. (2013) for porous single crystals at infinitesimal strains to finite strains, incorporating the evolution of void volume fraction and strain hardening of single crystal matrix. The model is assessed through three-dimensional unit cell finite element simulations based on periodic homogenisation and loading paths with prescribed constant stress triaxiality. The unit cell simulations are performed for face-centered cubic crystals with various crystallographic orientations, stress triaxialities and initial void volume fractions, showing the competitive influence of the stress triaxiality and the crystallographic orientation on the effective behaviour and the void volume evolution. The proposed model captures the hierarchy of porous single crystal responses with respect to crystal orientation and void volume fraction. It represents a remarkable compromise between description of unit cell behaviour and tractability in the computation of structural components. Highlights: A constitutive model for porous single crystals at finite strains and its finite element implementation are presented. The model capabilities are assessed by means of unit cell simulations including strain hardening and void growth. Fields of plastic slip and lattice rotation around the growing hole are provided for various crystal orientations. The model predicts the hierarchy in stress strain responses, void growth rate and onset to coalescence. It accounts for the effect of crystal orientation, void volume fraction and stress triaxiality. The plasticity at a notch in a porous single crystal is finally predicted depending on crystal orientation.